Evolutionary dynamics of immune-related genes and pathways in disease-vector mosquitoes. - Waterhouse, R; Kriventseva, E; Meister, S; Xi, Z; Alvarez, K; Bartholomay, L; Barillas-Mury, C; Bian, G; Blandin, S; Christensen, B; Dong, Y; Jiang, H; et al. (2007)
Mosquitoes are vectors of parasitic and viral diseases of immense importance for public health. The acquisition of the genome sequence of the yellow fever and Dengue vector, Aedes aegypti (Aa), has enabled a comparative phylogenomic analysis of the insect immune repertoire: in Aa, the malaria vector Anopheles gambiae (Ag), and the fruit fly Drosophila melanogaster (Dm). Analysis of immune signaling pathways and response modules reveals both conservative and rapidly evolving features associated with different functional gene categories and particular aspects of immune reactions. These dynamics reflect in part continuous readjustment between accommodation and rejection of pathogens and suggest how innate immunity may have evolved.